DESIMINASI TEKNOLOGI BUDIDAYA PADI BERAS MERAH VARIETAS IMPAGO UNRAM I PADA KELOMPOK TANI LANGGEM SARI DESA SAMA GUNA KECAMATAN TANJUNG KABUPATEN LOMBOK UTARA - I Gusti Putu Muliarta Aryana; I Wayan Sudika; Anak Agung Ketut Sudhramawan; Ni Wayan Sri Suliartini (Universitas Mataram, 2023)
In order to maintain West Nusa Tenggara as a national rice granary and participate in maintaining national rice self-sufficiency, it is necessary to introduce cultivation technology and superior varieties of red rice, namely Impago Unram I. The problem encountered by partner farmer groups is that they do not know about rice. Red rice variety Impago Unram I regarding benefits and cultivation technology. The method used in this program is a training method followed by practical work in the field and active participatory action research (participatory action research). The implementation period starts from February to May 2023. The activity stages include providing training for 1 day in Langgem Sari hamlet, Sama Guna village. Field laboratory practice (Demplot) regarding planting row legowo 4:1, using optimum seed age on a 10 acre land area owned by members of a farmer group. Evaluation to measure the success of this activity is carried out through participant responses when delivering theory/training, participant responses during field practice and observations in field laboratory plots. The results of the activity showed that members of the Langgem Sari farmer group in Sama Guna village understood the description of the Impago Unram I variety of red rice, the content and benefits of red rice for health, and understood the Red Rice Cultivation Technology using the Jajar Legowo 4:1 pattern as a result. counseling is carried out. Farmers are able to practice cultivating red rice of the Impago Unram I variety from seed soaking, seeding, planting, maintenance to harvest, through demonstration plot activities and mentoring. Farmers will plant red rice next season and it is hoped that the team will look for market opportunities.